2010
DOI: 10.3844/jssp.2010.162.166
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Dominance, Marital Satisfaction and Female Aggression

Abstract: Problem statement: Several studies conducted on dominance, marital satisfaction and female aggression (physical and psychological) are the primary concern of the review done in this study. This article contains two parts; the first part touches on the findings which show female dominance has relationship with aggression. The second section is concerned on studies which have shown marital satisfaction has correlation with female aggression. According to the existing literature, the rate of female aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In several studies, it was indicated that women with temporary marriage mostly suffered from psychosocial issues causing two types of concerns including 1) intrapersonal communication disorders (e.g., anxiety, depression, and lack of self-esteem) and 2) interpersonal communication disorders (e.g., a lack of love and empathy) 61 , 62 . Numerous studies reported STIs, sexual abuse, unwanted pregnancy, and abortion as several possible outcomes of temporary marriage 63 .…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, it was indicated that women with temporary marriage mostly suffered from psychosocial issues causing two types of concerns including 1) intrapersonal communication disorders (e.g., anxiety, depression, and lack of self-esteem) and 2) interpersonal communication disorders (e.g., a lack of love and empathy) 61 , 62 . Numerous studies reported STIs, sexual abuse, unwanted pregnancy, and abortion as several possible outcomes of temporary marriage 63 .…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, as presented by Edalati and Redzuan in a review article, sexual and/or marital dissatisfaction are responsible for aggressiveness in women/wife. Women that dissatisfied with their marital were more likely to use physical aggression [26].…”
Section: Discussionmentioning
confidence: 99%